If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(8x + 3) + -5 = 2(6x + 8) + 1 Reorder the terms: 4(3 + 8x) + -5 = 2(6x + 8) + 1 (3 * 4 + 8x * 4) + -5 = 2(6x + 8) + 1 (12 + 32x) + -5 = 2(6x + 8) + 1 Reorder the terms: 12 + -5 + 32x = 2(6x + 8) + 1 Combine like terms: 12 + -5 = 7 7 + 32x = 2(6x + 8) + 1 Reorder the terms: 7 + 32x = 2(8 + 6x) + 1 7 + 32x = (8 * 2 + 6x * 2) + 1 7 + 32x = (16 + 12x) + 1 Reorder the terms: 7 + 32x = 16 + 1 + 12x Combine like terms: 16 + 1 = 17 7 + 32x = 17 + 12x Solving 7 + 32x = 17 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 7 + 32x + -12x = 17 + 12x + -12x Combine like terms: 32x + -12x = 20x 7 + 20x = 17 + 12x + -12x Combine like terms: 12x + -12x = 0 7 + 20x = 17 + 0 7 + 20x = 17 Add '-7' to each side of the equation. 7 + -7 + 20x = 17 + -7 Combine like terms: 7 + -7 = 0 0 + 20x = 17 + -7 20x = 17 + -7 Combine like terms: 17 + -7 = 10 20x = 10 Divide each side by '20'. x = 0.5 Simplifying x = 0.5
| 5+x+7= | | 3.1x+2.9x=-6 | | -17y-9y+18=-8 | | x+y+z+u=10 | | z=50x+60y | | 10x-17=6x+2 | | 5(m-3)=7 | | 5m+7=5m+s+1 | | 9x+3x-4x=54 | | x+6.3=9.9 | | 16b-6.5=8.5 | | 6(2a+7)-10= | | 9(x-5)+8= | | 8In(3x)=32 | | 6(x+7)-20=6y | | -8x+2x-16-5x+7x= | | 24=14+3(x+8) | | 60=2d+d+30 | | 5x+6x+3+8=7x+5+3x | | -0.6*6= | | Y=20sin(3x) | | 2b-4-4b-6= | | 6a-3c= | | 36x-4=4x | | 8-(2+x)=0 | | 59-2x=5-8x | | X^2-3x=-2.25 | | 5x^3+8x^2-2=0 | | 6(a+8)=56 | | 90=5x+3y | | Y=4(x+45)+3x | | 2x-4+90=180 |